2018
DOI: 10.1101/279620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thirty clues to the exceptional diversification of flowering plants

Abstract: 15• The identified deep time diversification shifts are clues to identify ultimate drivers of angiosperm megadiversity, which probably involve multivariate interactions among intrinsic traits and extrinsic forces. An enhanced understanding of angiosperm diversification will involve a more precise phylogenetic location of diversification shifts, and integration of fossil information. 35

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Three of the four broad accelerations of diversification we detected in monocots accord with one or more previous studies (Givnish et al, 2015;Spriggs et al, 2015;Magallón et al, 2018). In general, however, there is scale dependence in the resolution of such accelerations.…”
Section: Monocot Timeline and Rates Of Net Species Diversificationsupporting
confidence: 89%
See 2 more Smart Citations
“…Three of the four broad accelerations of diversification we detected in monocots accord with one or more previous studies (Givnish et al, 2015;Spriggs et al, 2015;Magallón et al, 2018). In general, however, there is scale dependence in the resolution of such accelerations.…”
Section: Monocot Timeline and Rates Of Net Species Diversificationsupporting
confidence: 89%
“…The general decline in numbers of diversification accelerations with the taxonomic breadth of studies may reflect a lower intensity of taxon sampling or fossil calibrations, or greater background-foreground contrasts in broader studies that impair ability to detect some accelerations. The accelerations identified by Magallón et al (2018) but not by us may reflect their inability to obtain correct tree resolution with far more limited sequence data (three plastid genes, 18S, 26S nrDNA): Arecales are not sister to Commelinales-Zingiberales, and Tecophilaeaceae are not part of the Asparagales clade sister to Doryanthaceae (Fig. 1).…”
Section: Monocot Timeline and Rates Of Net Species Diversificationmentioning
confidence: 76%
See 1 more Smart Citation
“…It has become increasingly clear that high diversification rates leading to extant angiosperm species diversity do not characterize angiosperms as a whole (Sanderson & Donoghue, ). Several angiosperm‐wide studies have relied on the increasingly well‐understood molecular phylogeny to detect exceedingly species‐rich clades (Magallón & Sanderson, ; Magallón & Castillo, ) or to investigate the placement and timing of diversification shifts, either by analyzing the distribution of species richness among terminals (Davies et al ., ; Smith et al ., ) or by using explicit birth–death models (Tank et al ., ; Magallón et al ., ). These studies have identified a partially overlapping set of diversification increases, scattered across the phylogeny.…”
Section: Six Key Questionsmentioning
confidence: 99%
“…Available information on phylogenetic relationships, time of origin and distribution of species richness among angiosperm clades indicates that, as in many other biological groups, among‐lineage distribution of diversity is highly heterogeneous. In many cases, a single or a few species‐poor branches form consecutive sister lineages to a megadiverse clade (‘depauperons’ sensu Donoghue & Sanderson, ), but other species‐poor lineages are immersed within a clade that is highly diverse (Magallón et al ., ). Depauperons are explained as lineages that diverged before or along the assembly of complex innovations in particular ecological and physical settings (‘synnovation’; Donoghue & Sanderson, ).…”
Section: Six Key Questionsmentioning
confidence: 99%